Approach to Development of Local Economic Capital to Increase the Capacity of Community Enterprise Entrepreneurs in The Lower Northern Region of Thailand - Phiwphun, Kaewta (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The research objectives were to: 1) analyze the causal relationship paths influencing local economic capital, 2) create guidelines for the development of local economic capital, and 3) examine guidelines for the development of local economic capital to increase the capacity of community enterprise entrepreneurs in the lower northern region of Thailand. The sample in this research was divided into 3 groups; the first was 360 people from community enterprises in the lower northern region of Thailand, the second was 5 key informants, and the third was 9 experts. Three types of research tools were used, comprising a questionnaire, a semi-structured interview form, and an assessment form. The data were analyzed using statistical techniques, structural equation modeling, mean, standard deviation, and content analysis. The results showed that 1) The causal correlation path analysis model was fairly consistent with the empirical data, considering the Chi-square Probability Level of 161.389, Relative Chi-square of 1.416, Goodness of Fit Index of .956, and Root Mean Square Error of Approximation of .026. 2) The development of local economic capital had a causal relationship with increasing competitiveness. As for the strategy of marketing mix and social capital, there was a direct causal relationship with local economic capital, and there was an indirect causal relationship with increased competitiveness transmitted through local economic capital. and 3) The guidelines in terms of the aspects of accuracy, appropriateness, feasibility, and usefulness overall were at the highest average level.